Emotion dysregulation as a maintenance factor for posttraumatic stress symptoms: The role of anxiety sensitivity. Issue 12 (11th May 2020) - Raudales, Alexa M.; Preston, Thomas J.; Albanese, Brian J.; Schmidt, Norman B.
Abstract: Objectives: The current study tested whether emotion dysregulation, assessed by the Difficulties in Emotion Regulation Scale (DERS), would predict posttraumatic stress symptoms (PTSS) through anxiety sensitivity (AS). Alternate cognitive‐affective mediators (i.e., distress tolerance and intolerance of uncertainty) were explored. Method: A total of 259 trauma‐exposed community members (ages averaging 37.39; evenly distributed by gender) from a larger clinical trial targeting suicide risk factors completed a clinical interview and self‐report questionnaires at baseline, Week‐3, and 1‐month follow‐up appointments. Results: AS at Week 3 significantly mediated the relationship between initial emotion dysregulation and 1‐month follow‐up posttraumatic stress symptoms (PTSS) after controlling for condition and baseline symptoms ( β  = .07; standard error = 0.03; 95% confidence interval = [0.01, 0.14]). Effects held for one out of six emotion dysregulation subscales. Distress tolerance and intolerance of uncertainty were not significant mediators ( p s > .05). Conclusions: This study demonstrates that emotion dysregulation may confer maintenance of PTSS through AS. Findings highlight potentially malleable targets for interventions.